2022
DOI: 10.1002/pat.5784
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of transport mechanism and nanostructure of nonperfluorinated PVA/sPTA proton exchange membrane for fuel cell application

Abstract: Polyvinyl alcohol (PVA) with sulfophthalic acid (sPTA) as a proton exchange membrane (PEM) for fuel cell applications was prepared by the solvent casting method.The fabricated membranes were obtained by varying the concentration of sPTA from 5 to 30 wt.% of PVA and thermally crosslinked at a temperature of 100 C for 1 h.Crosslinked PVA/sPTA membranes were characterized by FTIR spectroscopy, scanning electron microscopy (SEM), and wide-angle X-ray diffraction (XRD). The transport properties were investigated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Relevant research can be found in ref. 93 , 94 , 95 , 96 , 97 , 98 . The yellow and purple clusters consist of 6 and 5 keywords, respectively, focusing on the preparation processes and methods of PEMs, as well as the development of emerging materials such as polyoxadiazoles, 99 sulfonated PI, 100 , 101 MoS 2 -NiO-Co 3 O 4 filled chitosan, 102 and branched polymer materials.…”
Section: Resultsmentioning
confidence: 99%
“…Relevant research can be found in ref. 93 , 94 , 95 , 96 , 97 , 98 . The yellow and purple clusters consist of 6 and 5 keywords, respectively, focusing on the preparation processes and methods of PEMs, as well as the development of emerging materials such as polyoxadiazoles, 99 sulfonated PI, 100 , 101 MoS 2 -NiO-Co 3 O 4 filled chitosan, 102 and branched polymer materials.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, owing to their characteristics, DMFCs are uniquely and well-suited for portable electronics in providing a small amount of power over a long period [7][8][9]. However, there are still many technical obstacles in the way of developing DMFCs, such as slow methanol electrooxidation and crossover through the polymer electrolyte kinetics [10][11][12][13]. Methanol crossover from the anode to the cathode reduces fuel utilisation and causes cathode depolarization [14].…”
Section: Introductionmentioning
confidence: 99%